2020
DOI: 10.21203/rs.3.rs-76663/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prognostic value of the SOFA score in patients with COVID-19: a retrospective, observational study

Abstract: Background Patients with Coronavirus disease 2019 (COVID-19) have a high mortality rate, and thus, it is particularly important to predict the severity and prognosis of COVID-19. The Sequential Organ Failure Assessment (SOFA) score has been used to predict the clinical outcomes of patients with multiple organ failure requiring intensive care. Therefore, we retrospectively analyzed the clinical characteristics, risk factors, and relationship between the SOFA score and the prognosis of COVID-19 patients. Method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Studies have shown that the SOFA score could be used to evaluate severity and 60-day mortality of COVID-19 with the optimal cut-off score of 5. 39 The limitations of this study include the variability of treatment provided in the multiple centres. The participants of this study may not comprise a true observational cohort, as this was a post hoc analysis of randomised controlled trial data and extrapolation to the general population must be carefully qualified.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that the SOFA score could be used to evaluate severity and 60-day mortality of COVID-19 with the optimal cut-off score of 5. 39 The limitations of this study include the variability of treatment provided in the multiple centres. The participants of this study may not comprise a true observational cohort, as this was a post hoc analysis of randomised controlled trial data and extrapolation to the general population must be carefully qualified.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that the SOFA score could be used to evaluate severity and 60-day mortality of COVID-19 with the optimal cut-off score of 5. 39 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, most of the contributions on predictive models for COVID-19 progression are hampered by either a somewhat limited access to data (typically, they are exclusively based on data from hospitalised or critical patients) or by the simplistic nature of the predictive models considered (which, of course, is often related to the limited access of useful data). As an example, [ 4 ] considers a wide collection of predictors but it is based on a very small sample of hospitalised patients. This reference uses Cox regression models, but with death as the only event of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a slightly better than expected in-hospital mortality and hypothesize that increased survival in our patients might be due to the established multidisciplinary and multisectoral pathway. Severity of COVID-19 infection and a higher SOFA seem to be strongly associated [10]. In this context, it should be noted that platelet count and parameter of liver injury (bilirubin) and kidney disease (serum creatinine) are part of the SOFA score, which furthermore comprises ventilation (oxygenation index) and circulation-support parameters (use of vasoactive medication), as well as Glasgow Coma Score value which is decreased in critically ill patients due to sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased disease severity in COVID-19 was found to be associated with demographic factors (higher age, male gender) and comorbidities such as, obesity, diabetes, hypertension and coronary heart disease [6]. The development of acute kidney injury (AKI) and increased SOFA score on admission are considered negative prognostic factors for clinical outcomes [7] [8,9] [10]. Moreover, increased white blood cell count, elevated level of C-reactive protein (CRP), Procalcitonin (PCT), Interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), lactate dehydrogenase (LDH) and signs of hypercoagulopathy (low platelet count and increased D-dimers, Fibrinogen and Prothrombin Time) were associated with higher severity and increased mortality of COVID-19 [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%